2011
DOI: 10.1177/0021955x11413659
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution X-ray computed tomography for 3D microstructure characterization of a cellulose particle filled polymer foam

Abstract: Due to the excellent strength/weight ratio, good energy absorbing ability, superior thermal, and acoustic insulation properties together with reasonable costs, polymer foams are the material of choice for many applications. The incorporation of particulate or fibrous fillers can even improve the properties. In this article, we investigate an opencell polyurethane foam filled with cellulose particles. This is a new moisture-absorbing wood-plastic composite used for special mattresses. The foam was characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Kastner et al. 48 observed regenerated cellulose particles embedded in PU foam cell struts using CT tomographs. They were able to isolate the cellulose using a series of image processing steps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kastner et al. 48 observed regenerated cellulose particles embedded in PU foam cell struts using CT tomographs. They were able to isolate the cellulose using a series of image processing steps.…”
Section: Introductionmentioning
confidence: 99%
“…47 Three-dimensional stereo microscopy and high-resolution X-ray computed tomography (CT) have been used to observe the fiber dispersion and cell morphology in fiber-reinforced foams. Kastner et al 48 observed regenerated cellulose particles embedded in PU foam cell struts using CT tomographs. They were able to isolate the cellulose using a series of image processing steps.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters are determined in the same way as described in Kastner et al (2011). 29 For the separation of the air and polymer phase, a global threshold method is utilized.…”
Section: Modelling Methodologymentioning
confidence: 99%
“…These parameters are determined in the same way as described in Kastner et al (2011). 29 For the separation of the air and polymer phase, a global threshold method is utilized. A threshold is chosen in this way that the air to polymer ratio equals the measured material density.…”
Section: Modelling Methodologymentioning
confidence: 99%
“…To characterize the foam morphology, surface microscopy techniques are usually employed including scanning electron microscopy (SEM) and optical microscopy. In these methods, cell size distribution and population density measurements are limited to specific 2D cross-section images, while the whole three-dimensional structure could be more complicated [10][11][12]. Therefore the cell morphology interpreted using 2D images might not be accurate.…”
Section: Introductionmentioning
confidence: 99%